2012
DOI: 10.4161/adip.19705
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dynamics of adipose cells

Abstract: Adipose cells are unique in the dynamism of their sizes, a requisite for their main function of storing and releasing lipid. Lipid metabolism is crucial for energy homeostasis. However, the regulation of lipid storage capacity in conditions of energy excess and scarcity is still not clear. It is not technically feasible to monitor every process affecting storage capacity such as recruitment, growth/shrinkage and death of individual adipose cells in real time for a sufficiently long period. However, recent comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 67 publications
1
33
0
1
Order By: Relevance
“…Adipocyte proliferation could, as well, be related to mature adipocyte size, as suggested by studies showing that on reaching a critical volume rat adipocytes secrete factors that recruit new adipocytes (Marques et al, 1998), increasing tissue storage capacity. Adipose cell size could be dependent on lipid fluxes or the rates of lipogenesis and lipolysis (Soula et al, 2013), which in turn could be related to cell surface area, larger cells being less efficient at lipid absorption/release than small cells (Jo et al, 2012). It follows from the above-mentioned findings that the nadir could be a function of the size-dependent growth of adipose cells coupled with size fluctuations associated with lipid turnover.…”
Section: Marbling and Adipositymentioning
confidence: 99%
See 1 more Smart Citation
“…Adipocyte proliferation could, as well, be related to mature adipocyte size, as suggested by studies showing that on reaching a critical volume rat adipocytes secrete factors that recruit new adipocytes (Marques et al, 1998), increasing tissue storage capacity. Adipose cell size could be dependent on lipid fluxes or the rates of lipogenesis and lipolysis (Soula et al, 2013), which in turn could be related to cell surface area, larger cells being less efficient at lipid absorption/release than small cells (Jo et al, 2012). It follows from the above-mentioned findings that the nadir could be a function of the size-dependent growth of adipose cells coupled with size fluctuations associated with lipid turnover.…”
Section: Marbling and Adipositymentioning
confidence: 99%
“…Despite recent gains in our comprehension of AT regulation in meat animals, many issues still need to be explained before this process is fully understood. At the same time, metabolic differences have been shown to underlie the anatomical origin of AT (Miller et al, 1991), and adipose cells are known to differ in their ability to uptake lipids and in their functional attributes (Jo et al, 2012). Differences between intramuscular (IM) and SC ATs at the molecular level could be expected as well, and for instance Pickworth et al (2011) observed higher levels of peroxisome proliferator-activated receptor γ (PPARG), fatty acid-binding protein 4 (FABP4), fatty acid synthase (FASN) and lipoprotein lipase (LPL), messenger RNA (mRNA) in SC than in IMF in feedlot cattle (Simmental-Angus crossbred).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative elucidation of the relationship of whole body fat mass changes, the macroscopic level, and adipose cellsize and number changes, the microscopic level, in response to physiological stimuli and energy intake is essential to understand the development of obesity, as adipose tissue state is historydependent. 9,10,12,13 However, little is known about the relationship between metabolic state, changes in macroscopic fat mass, and associated changes in microscopic adipose tissue morphology.…”
Section: Introductionmentioning
confidence: 99%
“…new cell recruitment, cell growth/shrinkage, lipid turnover, and cell death) can lead to changes in adipose cell-size distributions over the life of an individual. 10,12,13 Correspondingly, a change in fat mass is associated with a change in the adipose cellsize distribution, which includes information on cell sizes and numbers. Quantitative elucidation of the relationship of whole body fat mass changes, the macroscopic level, and adipose cellsize and number changes, the microscopic level, in response to physiological stimuli and energy intake is essential to understand the development of obesity, as adipose tissue state is historydependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation